2016
DOI: 10.1111/pan.12877
|View full text |Cite
|
Sign up to set email alerts
|

Pulmonary aspiration under GA: a 13‐year audit in a tertiary pediatric unit

Abstract: The incidence of aspiration under general anesthesia in our hospital is comparable to published reports. Our audit highlights the fact that pulmonary aspiration although rare mostly occur in healthy ASA 1 and 2 children with no prior history. Emergency surgeries put the patient at a higher risk of aspiration. They occurred usually during induction, a process which tends to be variable (in technique and duration) for pediatric patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
56
4
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 48 publications
(66 citation statements)
references
References 9 publications
5
56
4
1
Order By: Relevance
“…Since perioperative aspiration is an extremely rare event and may depend on the patient populations studied as well as the clinical practice at each institution, it is possible that risk factors may vary between centers, complicating the prediction of aspiration risk. For example, aspiration was noted in our study to occur with equal likelihood during induction as during maintenance, which is in contrast to prior findings regarding timing . In comparing our outcome with previously published findings from years ago, it should also be noted that practices and medications have changed substantially over the past several decades.…”
Section: Discussioncontrasting
confidence: 78%
See 1 more Smart Citation
“…Since perioperative aspiration is an extremely rare event and may depend on the patient populations studied as well as the clinical practice at each institution, it is possible that risk factors may vary between centers, complicating the prediction of aspiration risk. For example, aspiration was noted in our study to occur with equal likelihood during induction as during maintenance, which is in contrast to prior findings regarding timing . In comparing our outcome with previously published findings from years ago, it should also be noted that practices and medications have changed substantially over the past several decades.…”
Section: Discussioncontrasting
confidence: 78%
“…In prior studies, several risk factors have been identified as being associated with perioperative pulmonary aspiration including higher ASA status, younger age, and emergent surgery . Such associations were not found in the present study.…”
Section: Discussioncontrasting
confidence: 71%
“…In many or most settings, ASA physical status 3 and 4 patients often receive anaesthesia when possible. Third, aspiration during general anaesthesia most frequently occurs during airway manoeuvres such as tracheal intubation and extubation, use of muscle relaxants and following positive pressure bag/mask ventilation which can cause gas insufflation of the stomach . Such high‐risk events are less relevant to procedural sedation, where they only occur as part of rescue for significant airway or respiratory adverse events.…”
Section: Resultsmentioning
confidence: 99%
“…Most studies observed that aspiration was more common during emergency surgery in adults , with mixed results in children .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation